A review of the crosswind effect on the natural draft cooling towers. (5th March 2019) - Li, Xiaoxiao; Gurgenci, Hal; Guan, Zhiqiang; Wang, Xurong; Xia, Lin
Highlights: Reviewed and discussed the cooling tower research methods. Explained the mechanism of the crosswind effect on natural draft cooling tower. Compared the mitigation methods on the crosswind issue. Abstract: Crosswind is a significant concern for the design and operation of a natural draft cooling tower. The negative effects of crosswind on the thermal performance of natural draft cooling towers have been shown in many cases, for a variety of tower types. This paper presents a comprehensive review to synthesize the current research status in this field. At first, three common cooling tower research methods used to quantify the crosswind effect: full-scale/field measurements, lab-scale tests and CFD modelling, are reviewed and discussed. Then, based on the existing literature, the crosswind effect and its working mechanism on different types of natural draft cooling towers are summarized and discussed. Finally, the most current findings and solutions to address the crosswind issue are reported. The main advantages and disadvantages of each solution are presented and discussed. The information collected in this review paper could be a useful guidance for the design and optimization of natural draft cooling tower.